PENGARUH PERCEIVED DESIRABILITY DAN PERCEIVED FEASIBILITY TERHADAP INTENSI BERWIRAUSAHA - Prihandani, Farid Hamzah; Nurlatifah, Hasnin Aulia; Nuriansyah, Fazar (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This study aims to determine the effect of perceived desirability and perceived feasibility on entrepreneurial intentions. The approach in the research used is a quantitative approach with the survey method. Data collection techniques used are through questionnaires distributed to respondents. The population in this study were all students of the Economic Education Study Program at the University of Education Indonesia. The data analysis techniques used include classical assumption tests, descriptive statistics, multiple linear regression tests and hypothesis testing. The results showed that: (i) perceived desirability, perceived feasibility and entrepreneurial intentions in Economic Education students of Universitas Pendidikan Indonesia are in the high category. (ii) perceived desirability has a positive effect on entrepreneurial intention (iii) perceived feasibility has a positive effect on entrepreneurial intention (iv) perceived desirability and perceived feasibility simultaneously have a positive effect on entrepreneurial intention.